Three year follow-up of an early childhood intervention: is movement skill sustained? - Zask Avigdor; Barnett Lisa M; Rose Lauren; Brooks Lyndon O; Molyneux Maxine; Hughes Denise; Adams Jillian; Salmon Jo (BMC, 2012)
Abstract Background Movement skill competence (e.g. the ability to throw, run and kick) is a potentially important physical activity determinant. However, little is known about the long-term impact of interventions to improve movement skills in early childhood. This study aimed to determine whether intervention preschool children were still more skill proficient than controls three years after a 10 month movement skill focused intervention: 'Tooty Fruity Vegie in Preschools'. Methods Children from 18 intervention and 13 control preschools in NSW, Australia were assessed at ages four (Time1), five (T2) and eight years (T3) for locomotor (run, gallop, hop, leap, horizontal jump, slide) and object control proficiency (strike, bounce, catch, kick, overhand throw, underhand roll) using the Test of Gross Motor Development-2. Multi-level object control and locomotor regression models were fitted with variables time, intervention (yes/no) and a time*intervention interaction. Both models added sex of child and retained if significant, in which case interactions of sex of child with other variables were modelled and retained. SPSS (Version 17.0) was used. Results Overall follow-up rate was 29% (163/560). Of the 137 students used in the regression models, 53% were female (n = 73). Intervention girls maintained their object control skill advantage in comparison to controls at T3 (p = .002), but intervention boys did not (p = .591). At T3, there were no longer intervention/control differences in locomotor skill (p = .801). Conclusion Early childhood settings should implement movement skill interventions and more intensively target girls and object control skills.